Chlamydia trachomatis infection and its associated factors among the infertility population - Baoqing DENG; Yunfeng YE; Ning NING; Ruilin YAN; Guichun WEN; Licheng HUANG; Yongzheng DENG; Qing YUAN; Yumao CAI; Xiangsheng CHEN (Pifu-xingbing zhenliaoxue zazhi, 2024)
Objective To reveal Chlamydia trachomatis (CT) infection and its associated factors among patients attending the infertility-related clinics in Bao'an District of Shenzhen in order to develop evidence-based strategies for interventions of CT in this population. Methods From April to December 2021, patients attending four infertility-related clinics in Bao'an District of Shenzhen were invited to participate in the survey using a recruitment approach. After an informed consent was obtained, each participant provided socio-demographic and behavioral information and urine samples for CT detection using a nucleic acid assay. Logistic regression was used to determine the factors associated with CT infection. Results Among a total of 954 participants, the prevalence of CT infection was 3.56%. The logistic analysis showed that the risk factors of CT included individuals aged younger than 25 years (OR=3.91, 95%CI: 1.58~9.67), having junior college education (OR=4.33, 95%CI: 1.23~15.24) and having more than 2 sexual partners in the last year (OR=4.25, 95%CI: 1.72~10.55). The participants (74.42%) were unaware of symptoms of CT infection and 73.90% never had any prior screening for CT. Conclusions The CT infection rate is relatively high among the infertility population in Bao'an District, Shenzhen. The sexually active age, relatively low educational level, and multiple sexual partners are risk factors for CT infection. At infertility clinics, CT screening along with health education should be given to people at high risk of CT infection in order to improve the reproductive health.